(untitled) (American Journal of Islam and Society, 2006)
Yvonne Corcoran-Nantes’ Lost Voices: Central Asian Women Confronting Transition examines how the Soviets empowered and disempowered Central Asian women before, during, and after the communist regime. To date, this book is the most in-depth study of the revolutionary transformations experienced by these women during the twentieth century. Combining her western academic background and sensitivity for the local context, she reaches beyond the mainstream conceptualization of gender issues vis-à-vis the Soviet regime to examine Central Asian and western literature on gender thematics across disciplines, from anthropology to political science. The book opens with a sophisticated analysis of the relation between western feminist paradigms and the Soviet policy of gender equality. Both existed in parallel, yet were interactive. Although western feminist ideas impacted women from the Soviet space, they represented rather marginal views among Soviet feminists. Corcoran-Nantes explains that while the Soviet regime was empowering Central Asian women by liberating them from traditional religious values and setting quotas in public structures, these radical shifts in daily life inevitably complicated their identities in various social situations. The Soviet model provided some institutional framework for the independence period, yet was largely inadequate in the new free market system. As a result, Central Asian women faced greater problems in shaping their feminist agendas when compared to Russian women. Chapter 2 discusses why this forceful emancipation, which involved khujun (unveiling), replacing Islamic law with Soviet legislation, and establishing zhensovets (women councils) in the 1920-30s, was controversial. She argues that women were expected to follow the changes, yet still had to play important social roles in their families. In addition, this empowerment provoked domestic and social violence against women. Such phenomena as khujun also engendered intra-personal conflict and hesitation among the first generation of Soviet-ruled Central Asian women. Corcoran-Nantes states that the “emancipation of Central Asian women had far more to do with the implementation of the Soviet political and economic project than constituting an act of altruism” (p. 38) ...